PENGARUH ENVIRONMENTAL, SOCIAL, DAN GOVERNANCE (ESG) DISCLOSURE TERHADAP FIRM VALUE PADA PERUSAHAAN TERINDEKS IDX30 - Margana, Nyoman Raynaldi Rizky; Wiagustini, Ni Luh Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.08.TAHUN.2024, 2024)
The company's value is a crucial indicator for both the company itself and investors. The optimization of a company's value can enhance shareholder satisfaction and maintain the long-term sustainability of the company. Currently, companies are expected to manage their financial and non-financial potential to enhance their value. Optimizing the company's value can enhance shareholder satisfaction and ensure the long-term sustainability of the company. One non-financial component of a company is its sustainability aspect through the implementation of Environmental, Social, and Governance (ESG) practices. This research aims to analyze the influence of Environmental Disclosure, Social Disclosure, and Governance Disclosure on firm value using a quantitative approach. The research population consists of 49 companies listed in the IDX30 index during the period 2018-2022. Subsequently, a sample of 9 companies was obtained, observed over five years based on purposive sampling criteria, which consistently includes companies in the IDX30 index and publishes sustainability reports. The data analysis method used multiple linear regression analysis, revealing that Environmental Disclosure significantly affects firm value negatively, while Social Disclosure significantly affects firm value positively, and Governance Disclosure has no significant effect on firm value.